Smart Solar Grass Cutter - Edi Tan, Davik; Ahmad Fauzi, Fatihah Zulaikha; Mohamad, Mahmod Abd Hakim; Onn, Nurfarahin (Multidisciplinary Applied Research and Innovation, 2025)
The Smart Solar Grass Cutter project exemplifies a pioneering initiative at the intersection of sustainable technology and lawn maintenance, offering a transformative solution for urban and suburban landscapes. There a several issues with the current lawnmowers that users using right now. Grass-cutting technology in the past was manually operated using hand tools such as scissors, which required more human effort and time to complete the operation. Furthermore, in the traditional process, there is also a need for more consistency in the grass. Equipped with a variety of sensors, including infrared and ultrasonic, the mower ensures safe and efficient obstacle detection and avoidance. The algorithms optimize cutting patterns by considering dynamic variables such as grass growth rates 1/8 to 1/4 inch per day and specific lawn characteristics, thereby maintaining a well-groomed lawn while maximizing 15%-23% energy efficiency. By utilizing solar energy, the project significantly reduces carbon emissions, dependence on fossil fuels, and noise pollution associated with traditional gas-powered mowers, aligning with global trends toward eco-conscious practices. Additionally, a specialized mobile application enhances user convenience by enabling remote monitoring and control of the mower, including scheduling cutting sessions and receiving real-time updates. Overall, the Smart Solar Grass Cutter project represents a significant advancement in sustainable lawn maintenance, combining solar energy and user-friendly technology to offer a cost-effective and environmentally friendly alternative to traditional grass-cutting methods, thus positioning itself as a leader in the green revolution of urban landscape care.